Getah Virus Infection Rapidly Causes Testicular Damage and Decreases Sperm Quality in Male Mice - Li, Fengqing; Zhang, Bing; Xu, Zhiwen; Jiang, Chaoyuan; Nei, Mincai; Xu, Lei; Zhao, Jun; Deng, Huidan; Sun, Xiangang; Zhou, Yuancheng; Zhu, Ling (Frontiers in Veterinary Science, 2022)
Geta virus is a zoonotic arbovirus that can cause infection in many animals. It can cause pyrexia and reproductive losses in animals. After mating with infected males, female mice showed fewer pregnancies, fewer live born, longer gestation period, and more stillbirths. The objective of this study is to find out whether that was due to reduced fertility after infection of male mice. Male mice were injected with 100×TCID50/0.1 mL in a volume of 100ul GETV in their hindquarter muscle, resulting in decreased semen quality and testicular histopathological changes, and the virus was detected in the testes. At 0.5 dpi (day post infection) , male mice showed decreased sperm density,motility and decreased serum testosterone concentration, increased sperm malformation rate, vacuoles in spermatogonial cells/spermatocytes in spermatogenic tubules, and the highest virus copies in testis. At 2dpi, the sperm density and motility reached the lowest value of 3.99×106/ mL and 62.03%, and the malformation rate reached 43.67%. At 28dpi, the sperm indexes of the experimental group gradually approached that of the control group, but there were still significant differences. Since then, histopathological changes have become progressively worse, with the most severe histopathological changes at 7dpi and gradual recovery. Up to 14dpi, the virus was detected by qRT-PCR and immunohistochemistry, which showed that the virus was only present in the testicular interstitium. GETV infection can rapidly enter the testis of mice and reduce the semen quality of mice, which needs to be paid attention to in the prevention and control of GETV.